2010
DOI: 10.1111/j.1467-8578.2010.00455.x
|View full text |Cite
|
Sign up to set email alerts
|

FOCUS ON PRACTICE: Living with children diagnosed with autistic spectrum disorder: parental and professional views

Abstract: The number of children diagnosed with an autistic spectrum disorder (ASD) is rising and is now thought to be as high as 1:100. While the debate about best treatment continues, the effects of having a child diagnosed with ASD on family life remain relatively unexplored. This article, by Karola Dillenburger of Queens University Belfast, Mickey Keenan of the University of Ulster, Alvin Doherty from the Health Service Executive Western Region, Tony Byrne of Parents' Education as Autism Therapists (PEAT) and Stephe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 41 publications
2
52
0
6
Order By: Relevance
“…Families and children with ASD need and deserve the best treatment that is evidence‐based (Morris, ). Yet many parents in the study reported here were dissuaded from using ABA‐based interventions by professionals who evidently were not as well informed as parents (Dillenburger, Keenan, Doherty, Byrne & Gallagher, ). The expense of privately funded home‐based ABA interventions was a problem.…”
Section: Discussionmentioning
confidence: 86%
“…Families and children with ASD need and deserve the best treatment that is evidence‐based (Morris, ). Yet many parents in the study reported here were dissuaded from using ABA‐based interventions by professionals who evidently were not as well informed as parents (Dillenburger, Keenan, Doherty, Byrne & Gallagher, ). The expense of privately funded home‐based ABA interventions was a problem.…”
Section: Discussionmentioning
confidence: 86%
“…This positive pro‐active public attitude is supported by parents' experiences (Lamb ; Dillenburger et al . , ) and scientific evidence (Helt et al ., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Bazı araştırma bulgularında ise, bu yeni ve zor durumun evlilikleri güçlendirdiği; aile bireylerine daha duyarlı ve sabırlı olma, hayata daha geniş perspektiften bakma gibi olumlu deneyimler ve kişisel kazançlar kattığı; yaşam için önemli bir amaç kazandırarak aile bireylerini güçlendirdiği ve tüm zorluklara rağmen çocuklarıyla ilgilenmenin ebeveynleri mutlu ettiği bildirilmektedir (Chang Yaz-2014 Cilt:13 Sayı:50 (96-111) www.esosder.org Summer-2014 Volume:13 Issue:50 98 ve McConkey, 2008;Gupta ve Singhal, 2004;Kenneth, Hodgson, McCammon ve Lamson, 2009;Üstüner Top, 2009). Bunların dışında bazı araştırma bulguları da; (a) ebeveynlerin psikolojik durumları üzerinde çeşitli değişkenlerin (örneğin, çocuktaki davranış sorunlarının yoğunluğu, ebeveynlerin kişiliği) etkili olduğunu (Dillenburger et al, 2010;Gupta ve Singhal, 2004;Gray, 2002) Yaz-2014 Cilt:13 Sayı:50 (96-111) www.esosder.org Summer-2014 Volume: …”
Section: Gđrđşunclassified